2021
DOI: 10.3390/met11081242
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Hollow Sample Setup Design for Mechanical Characterisation of Gaseous Hydrogen Embrittlement of Pipeline Steels and Welds

Abstract: This work discusses the design and demonstration of an in-situ test setup for testing pipeline steels in a high pressure gaseous hydrogen (H2) environment. A miniature hollow pipe-like tensile specimen was designed that acts as the gas containment volume during the test. Specific areas of the specimen can be forced to fracture by selective notching, as performed on the weldment. The volume of H2 used was minimised so the test can be performed safely without the need of specialised equipment. The setup is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To characterise the effect of gaseous hydrogen on Inconel 718, the sample design developed by Boot et al [40] (shown in Figure 3) for slow strain rate tensile (SSRT) test was used. This design has the advantage that the sample acts as the gas containment volume throughout the experiment, thus avoiding the need for autoclaves and sophisticated equipment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To characterise the effect of gaseous hydrogen on Inconel 718, the sample design developed by Boot et al [40] (shown in Figure 3) for slow strain rate tensile (SSRT) test was used. This design has the advantage that the sample acts as the gas containment volume throughout the experiment, thus avoiding the need for autoclaves and sophisticated equipment.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of hydrogen embrittlement is measured as the relative reduction of area of samples tested in nitrogen (%RAN2) and hydrogen (RAH2) environment [40]: The SSRT tests were performed in both nitrogen (N 2 ) and hydrogen (H 2 ) environments, with a pressure of 150 bar at 25 • C. Two repetitions were performed for each testing condition for repeatability. For the hydrogen tests, the samples were additionally charged for 48 h before the test to allow for hydrogen diffusion within the sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure is based on a tubular specimen exposed to high-pressure H in the inner machined hole; it was firstly proposed by Chandler and Walter 818 and has been also adopted by other authors. 819,820 The comparison with conventional tensile specimens can be hindered by the inner surface roughness 821 and by the different necking mechanisms during ductile failure. 748,822 The small punch test (SPT), which is commonly used as a screening tool for nuclear materials, requires a simple procedure to test miniature specimens, 10 × 10 × 0.5 mm 3 approximately, and it has been recently standardized (ASTM E3205-20 or BS EN 10371:2021) for metallic materials.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…For example, to circumvent the need of an autoclave containing a high volume of gaseous H 2 at high pressure, hollow specimens have been proposed as a safer and simpler alternative. This procedure is based on a tubular specimen exposed to high-pressure H in the inner machined hole; it was firstly proposed by Chandler and Walter and has been also adopted by other authors. , The comparison with conventional tensile specimens can be hindered by the inner surface roughness and by the different necking mechanisms during ductile failure. , …”
Section: Knowledge Base About Hementioning
confidence: 99%